SISTEM INFORMASI AKUNTANSI PENJUALAN MAKANAN RINGAN BERBASIS WEB DI KRENIES INDONESIA - Fitria Anjarwati; Oetari Febriyanti; Muthmainah; Candra Mecca Sufyana (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
Krenies Indonesia is a snack food supplier company for resellers - resellers inIndonesia. That way sales at Krenies Indonesia are very important to know theturnover in the form of sales reports, as a promotional medium, and orders.Unfortunately, recording and processing Krenies Indonesia sales data are stillmanual, so it takes a relatively long time. To optimize the computer technology thatis already available, the purpose of this study is to build a design of a snack salesinformation system using a website as a medium for promotion, recording, andreporting of sales. The data collection method that the researcher uses is interviews,observations, literature studies, and internet studies. This system approach methoduses a prototype that has advantages in developing the system to be made, time andcommunication to the user will play an active role. By designing Data FlowDiagrams (DFD) and using the PHP programming language and Mysql database,it produces 2 features or facilities, namely for admins and for customers. Processingand recording sales make it easier for admins and customers to place orders.